Remedial students' refusal of preferring English department as a major field of study at Madda Walabu University: students' outlook compared to the policy - Misgana Duresa; Tessema Tadesse; Zeleke Regasa (Frontiers in Education)
The purpose of this study was to find out remedial students' refusal to prefer the English department as a major field of study. The study participants were 99 students who were purposively chosen. For the study, descriptive case study design with a quantitative approach was used. Data was gathered using questionnaires. Using Statistical Package for Social Science (SPSS) version 25, mean and standard deviation were calculated and expressed in words. The findings revealed that there was lack of students' understanding of the advantages of studying English. Other obstacles that hindered students joining the English department were: considering English as the toughest subject, studying aimlessly, lack of exposure to lower grades, lack of guidance from parents and classmates, and believing that there are fewer career opportunities majoring in English. They also received less guidance or rigorous practice. Thus, teachers should play their role in advocating the benefit of joining the English department to attract first-year students who complete the remedial program to the English department.